About speech as the main subject of speech study (Eurasian Journal of Philology Science and Education, 2015)
This article considers the problem of speech study as the main object of science that studies the phenomenon of speech. Through in-depth review of the scientific concepts of the term it extends scientific assumptions about human coinages. The author touches upon the fact that in this area of expertise so many unresolved issues, including the definition of the object of study of speech study, scientific and theoretical questions about the meta-language of science, so the construction of a general scientific theory, the disclosure of a practical problem, the definition of the main goals and objectives - one of the primary and urgent problems requiring immediate solutions to modern Kazakh linguistics. The nature of speech and the process of its generation are particularly difficult, and therefore the knowledge of the word as an intellectual, psycho-physiological, psycholinguistic and aesthetic phenomenon is the principal task in determining its essential nature.
Keywords: speech; speech study; concepts; association experiment; concept; psycholinguistics; linguistics.